Halal Tourism in Kampung Al-Munawar, Palembang: Analysis with the Global Muslim Index Travel Approach - Nilawati Nilawati; M Fahry Zaiman; Rr Rina Antasari; Fauziah Fauziah (UNIVED Press, 2024)
This research aims to look at the development of halal tourism in Kampung Al-Munawar, Palembang, South Sumatra based on the GMTI (Global Muslim Index Travel) halal tourism standards with ACES (Access, Communication, Environment, and Services) assessments. This type of research is qualitative. The data source used is primary data resulting from observations and interviews with the people of Al-Munawwar Village, Palembang. This research found that development in Kampung Al-Munawar using the ACES (Access, Communication, Environment, and Services) method can be seen that some of the development criteria in Kampung Al-Munawar are good and some can be categorized as bad but close to sufficient.